2022
DOI: 10.3390/polym14225014
|View full text |Cite
|
Sign up to set email alerts
|

The Alterations and Roles of Glycosaminoglycans in Human Diseases

Abstract: Glycosaminoglycans (GAGs) are a heterogeneous family of linear polysaccharides which are composed of a repeating disaccharide unit. They are also linked to core proteins to form proteoglycans (PGs). GAGs/PGs are major components of the cell surface and the extracellular matrix (ECM), and they display critical roles in development, normal function, and damage response in the body. Some properties (such as expression quantity, molecular weight, and sulfation pattern) of GAGs may be altered under pathological con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 264 publications
0
24
0
Order By: Relevance
“…1 HS thus fulfills a particularly wide range of functions, during both developmental and physiological processes, including cell adhesion, migration, proliferation and differentiation, cellular signaling, extracellular matrix assembly, but also during numerous pathological disorders, such as cancer or infectious and neurodegenerative diseases. [2][3][4][5][6][7][8] A wealth of studies showed that protein binding to HS relies on specific saccharide domains, patterned along the polymer backbone during biosynthesis, [9][10][11][12][13] but the mechanism by which these saccharide domains are assembled remains poorly understood. The HS polymer is first elongated by the EXT1-EXT2 complex that catalyzes the alternative addition of a glucuronic acid (GlcA) and an N-acetylglucosamine (GlcNAc) molecule [14][15][16] and then structurally diversified by a set of Golgi-localized enzymes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 HS thus fulfills a particularly wide range of functions, during both developmental and physiological processes, including cell adhesion, migration, proliferation and differentiation, cellular signaling, extracellular matrix assembly, but also during numerous pathological disorders, such as cancer or infectious and neurodegenerative diseases. [2][3][4][5][6][7][8] A wealth of studies showed that protein binding to HS relies on specific saccharide domains, patterned along the polymer backbone during biosynthesis, [9][10][11][12][13] but the mechanism by which these saccharide domains are assembled remains poorly understood. The HS polymer is first elongated by the EXT1-EXT2 complex that catalyzes the alternative addition of a glucuronic acid (GlcA) and an N-acetylglucosamine (GlcNAc) molecule [14][15][16] and then structurally diversified by a set of Golgi-localized enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…There, it regulates the local concentration, stability, conformation, and biological activity of numerous protein ligands, including most cytokines, morphogens, growth factors and their receptors, enzymes, cellular adhesion, and extracellular matrix proteins as well as many proteins involved in host–pathogen interactions 1 . HS thus fulfills a particularly wide range of functions, during both developmental and physiological processes, including cell adhesion, migration, proliferation and differentiation, cellular signaling, extracellular matrix assembly, but also during numerous pathological disorders, such as cancer or infectious and neurodegenerative diseases 2–8 …”
Section: Introductionmentioning
confidence: 99%
“…GAGs are linear polyanionic animal heteropolysaccharides, which can be classified into four groups according to the structure of disaccharide units: heparin/heparin sulfate, chondroitin/chondroitin sulfate, keratin sulfate, and HA ( Song Y. et al, 2021 ). PGs are a class of modified proteins formed by the covalent binding of GAGs (such as chondroitin sulfate or heparin sulfate chains) other than HA to the protein core ( Wang and Chi, 2022 ; Purushothaman et al, 2023 ). PGs have been shown to enhance the remodeling capacity of liver tissue, and their numbers are significantly increased in cirrhotic liver tumors, especially perlecan and decorin, and the knockout of perlecan and decorin also leads to a decrease in ECM stiffness ( Kovalszky et al, 1993 ; Kimura et al, 2008 ; Robinson et al, 2017 ).…”
Section: Extracellular Matrix Remodeling In Hepatic Fibrosismentioning
confidence: 99%
“…As a consequence of its polyanionic character, HS interacts with hundreds of proteins and plays a crucial role in many biological processes. [5] Changes in the degree of sulfation (either under or over-sulfation) are also associated with several diseases [6] and may direct the location or activities of proteins. [7] Efforts to decipher structure-function relationships of HS-protein interactions and develop the therapeutic potential of HS-mimicking oligosaccharides [8] and glycopolymers [9] are hindered by the complexity and microheterogeneity of HS and a lack of tools to manipulate specific HS-protein interactions.…”
Section: Introductionmentioning
confidence: 99%